EARTH GEOGRAPHY FORM 500 TO 400 MILLION YEARS AGO: A FAUNAL AND PALAEOMAGNETIC REVIEW - Cocks L.R.M.; Torsvik T.H. (My University, 2002)
Very different palaeogeographical reconstructions have been produced by a combination of palaeomagnetic and faunal data, which are re-evaluated on a global basis for the period from 500 to 400 Ma, and are presented with appropriate confidence (or lack of it) on six maps at 20 Ma intervals. The palaeomagnetic results are the most reliable for establishing the changing palaeolatitudes of Baltica, Laurentia and Siberia. However, global palaeomagnetic reliability dwindles over the 100 Ma, and more evidence for relative continental positioning can be gleaned from study of the distribution of the faunas in the later parts of the interval. The new maps were generated initially from palaeomagnetic data when available, but sometimes modified, and terranes were positioned in longitude to take account of key faunal data derived from the occurrences of selected trilobites, brachiopods and fish. Kinematic continuity over the long period is maintained. The many terranes without reliable palaeomagnetic data are placed according to the affinities of their contained fauna. The changing positions of the vast palaeocontinent of Gondwana (which has hitherto been poorly constrained) as it drifted over the South Pole during the interval have been revised and are now more confidently shown following analysis of both faunal and palaeomagnetic data in combination, as well as by the glacial and periglacial sediments in the latest Ordovician. In contrast, the peri-Gondwanan and other terranes of the Middle and Far East, Central Asia and Central America are poorly constrained.